2015
DOI: 10.1002/hyp.10553
|View full text |Cite
|
Sign up to set email alerts
|

Predicting landscape sensitivity to present and future floods in the Pacific Northwest, USA

Abstract: Floods are the most frequent natural disaster, causing more loss of life and property than any other in the USA. Floods also strongly influence the structure and function of watersheds, stream channels, and aquatic ecosystems. The Pacific Northwest is particularly vulnerable to climatically driven changes in flood frequency and magnitude, because snowpacks that strongly influence flood generation are near the freezing point and thus sensitive to small changes in temperature. To improve predictions of future fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…However, increased warming has led to significant reductions in mountain snowpack accumulation and earlier snowmelt throughout the western U.S. Mote et al, 2005;Harpold et al, 2012). As a result, declines in dry season streamflow (Luce and Holden, 2009;Safeeq et al, 2013), earlier streamflow timing (Stewart et al, 2005;Maurer et al, 2007), and altered flood risk due to a potential increase in peakflow (Hamlet and Lettenmaier, 2007;Tohver et al, 2014;Safeeq et al, 2015a) have been reported across the region. As temperatures continue to warm, much of the region is expected to experience a shift from 1 solid (i.e., snow) to liquid (i.e., rain) phase precipitation (Knowles et al, 2006;Klos et al, 2014;Safeeq et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…However, increased warming has led to significant reductions in mountain snowpack accumulation and earlier snowmelt throughout the western U.S. Mote et al, 2005;Harpold et al, 2012). As a result, declines in dry season streamflow (Luce and Holden, 2009;Safeeq et al, 2013), earlier streamflow timing (Stewart et al, 2005;Maurer et al, 2007), and altered flood risk due to a potential increase in peakflow (Hamlet and Lettenmaier, 2007;Tohver et al, 2014;Safeeq et al, 2015a) have been reported across the region. As temperatures continue to warm, much of the region is expected to experience a shift from 1 solid (i.e., snow) to liquid (i.e., rain) phase precipitation (Knowles et al, 2006;Klos et al, 2014;Safeeq et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…As temperatures continue to warm, much of this region is expected to experience a shift from solid to liquid phase precipitation (Knowles et al , ). More precipitation falling as rain instead of snow, and consequently a lower total snowfall to precipitation ratio (hereinafter referred to as snow fraction, S f ), would affect total snow accumulation and the timing of snowmelt and runoff regimes, potentially leading to higher winter floods and lower flow in late spring and summer (Safeeq et al , , ). In any given region, however, changes in S f would depend on overall climatic regime as well as the corresponding changes in temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is likely to influence both streamflow [1920] and water temperature [3], thereby increasing the potential for physiological stress in fish populations [21]. Using the ichthyograph, managers can not only identify points in a species’ life cycle where hydrologic conditions may already be reaching physiological limits, but also determine whether future conditions are expected to lie outside the hydrologic conditions experienced in the past, and may represent critically-vulnerable time periods in a species’ life history.…”
Section: Discussionmentioning
confidence: 99%